PENDAMPINGAN eSPT PPh 21 SESUAI UU No.7 (2021) PADA CV MAJU MAKMUR BERSAMA - Holly, Anthony; Jao, Robert; Mardiana, Ana (Jurnal BALIRESO, 2023)
CV Maju Makmur Bersama is a profit-oriented firm which holds a culinary Korean food franchisee. The employee of CV Maju Makmur Bersama is 20 persons who get various income. In line with the dynamic of tax, regulation changed over time. Following business conditions, CV Maju Makmur Bersama, as a taxpayer, needs to adjust its tax obligation activity, especially ini Income tax Article 21deduction. Law Number 7 of 2021, known as the Law of Harmonization of Tax Regulation, has changed some tax regulations, especially in Income Tax Article 21 in the progressive tax rate bracket stated in Income Tax Article 17, where before the new regulation had four brackets and changed to 5 brackets also changing in the first bracket interval from fifty million to sixty million rupiahs. This caused a firm must recount the tax deduction from employer to employees. Hence, the employees are not disappointed, and employers, as taxpayers, can do their obligation correctly according to current tax regulations. Therefore, servants accompany the firm partner in implementing tax regulation, especially implementing income tax article 21 as stated in law Number 7 of 2021.